Improvement of Resistance to Fusarium Root Rot through Gene Pyramiding in Common Bean - Obala, J.; Mukankusi, C.; Rubaihayo, P.R.; Gibson, P.; Edema, R. (African Crop Science Journal, 2012)
Fusarium root rot (FRR), caused by Fusarium solani f.sp. phaseoli, is one of the most serious root rot diseases of common bean (Phaseolus vulgaris L.) throughout the world. Yield losses of up to 84% have been attributed to the disease. Development and deployment of resistant materials is the most feasible approach to managing the disease. The objective of this study was to estimate the number of pyramided Fusarium root rot resistance genes among the four resistant lines and determine their effectiveness in improving levels of resistance to Fusarium root rot in the susceptible bean cultivars. Crosses among four Fusarium root rot (Fusarium solani f.sp. phaseoli) resistant common bean (Phaseolus vulgaris) were developed. They involved six inbred lines, MLB-48-89A (M48), MLB-49-89A (M49), G2333 (G2) and G685 (G6), and two susceptible cultivars, K20 and Kanyebwa, The resistant lines were used to develop a double cross (DC) population. The DC F1 and each resistant parent were crossed to each of the two susceptible cultivars to form five-parent and single crosses, respectively. Developed populations were subjected to Fusarium solani f. sp. phasoeli isolate-3 under screenhouse conditions. There were segregation ratios of 15:1 (χ2 = 1.89, P = 0.17), 61:3 (χ2 = 0.18, P = 0.67) and 249:7 (χ2 = 1.74, P = 0.19) indicating that two, three and four genes independently condition resistance to F. solani in lines G2 x G6, M49 x M48 and (M49 x M48) x (G2 x G6). A good fit of only four genes in the double cross compared to two in the G2 x G6 , and three genes in the M49 x M48 cross suggests that at least one parent in the G2 x G6 cross have the same or closely linked genes as a parent in the M49 x M48 cross. The F1 means of the five-parent cross (FPC) involving either susceptible parent had lower disease scores, though not significantly (P > 0.05), than the single-crosses from that parent. The F2 of both FPC showed less disease than the single-cross (SC) means (P < 0.05) compared to the single-cross (SC) while the F2 of both FPC had a significant negative deviation (P < 0.05). The F2 frequency distributions also showed that the FPC in both Kanyebwa and K20 populations had higher proportions of resistant plants than any of the single crosses in the respective populations. The superior performance of the FPC over the SC demonstrates that combining resistance genes form different FRR resistance sources can provide a stable source of resistance than using single sources of resistance.
Keywords: Fusarium solani; Kanyebwa; Phaseolus vulgaris